Memorandum of Understanding between the Korea Development institute School of Public Policy and Management (KDI School) and Institute of Governance Studies, BRAC University (IGS, BU) (2009) - Korea Development School of public policy and management; Institute of Governance Studies, BRAC University (Korea Development School of public policy and management and IGS , BRAC University, 2013)
Korea Development Institute School o f Public Policy and Management (KDI School) and Institute o f Governance Studies, BRAC University (IGS, BU) (collectively referred to herein as the “Parties”) have agreed to sign this Memorandum o f Understanding (Memorandum), which represents a statement of intent by the parties to work together, and outlines the basis for collaboration and joint activities in fields o f mutual interest.